Development and validation of stability indicating liquid chromatographic (RP-HPLC) method for estimation of ubidecarenone in bulk drug and formulations using quality by design (QBD) approach (Brazilian Journal of Pharmaceutical Sciences, 2017)
A novel, accurate, precise and economical stability indicating Reverse Phase-High Performance Liquid Chromatography (RP-HPLC) method, was developed and validated for the quantitative determination of ubidecarenone (UDC) in bulk drug, UDC marketed formulation and UDC loaded cubosomes (CBMs) nanocarriers through Response surface methodology (RSM) design with three factors and three levels was performed to optimize the chromatographic variables followed by forced degradation studies of UDC were performed to detect degradation peak. RP-HPLC separation was achieved using mobile phase consisting of Acetonitrile:Tetrahydrofuran:Deionised water in the ratio 55:42:3 and a flow rate of 1.0 mL/min was optimized with a standard retention time (Rt) of 2.15 min, through experiment. The method was found linear in the concentration range of 5-100 µg/mL with a regression coefficient of 0.999. The limit of detection (LOD) and limit of quantification (LOQ) were found to be 3.04 µg/mL and 9.11 µg/mL, respectively.